If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + 7 = 12 + 5p Reorder the terms: 7 + 6p = 12 + 5p Solving 7 + 6p = 12 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. 7 + 6p + -5p = 12 + 5p + -5p Combine like terms: 6p + -5p = 1p 7 + 1p = 12 + 5p + -5p Combine like terms: 5p + -5p = 0 7 + 1p = 12 + 0 7 + 1p = 12 Add '-7' to each side of the equation. 7 + -7 + 1p = 12 + -7 Combine like terms: 7 + -7 = 0 0 + 1p = 12 + -7 1p = 12 + -7 Combine like terms: 12 + -7 = 5 1p = 5 Divide each side by '1'. p = 5 Simplifying p = 5
| 5+6c=10+3c | | 11x+21=3x+27 | | 9r^2+3r=0 | | 3+6c=10c+5 | | -6x+8=11 | | 3c+6=10+5c | | x^2+14x+9=0 | | 9x-(4x-8)=53 | | 5x-(6x+9)=11 | | 3+3c+3=5+5c+5 | | 3+3c=5+5c | | 9x=7x+22 | | 3+3=5+5 | | -10=-5W-25 | | 2x^2+x=210 | | (4+5C)+6=50 | | -2(x+21)=5(x-7) | | (b+8)(x)=5x-7 | | -6x+7y=3 | | 6b(x)=5x-7 | | -1.8(x)=5x-7 | | .33y+-0.50=.16y | | 0(x)=5x-7 | | 42=3x-35 | | 1(x)=5x-7 | | x^2=121 | | 3(3m-2)=2(3m+3) | | 2x^2+x=212 | | 10xy+15y*2+8wx+12wy=(2x+3y)(5y+4w) | | 12x-4+42=17x+8 | | -6-20=-2n+4(1-3n) | | 2(8-x)=2x+16 |